Proceedings of the 2011 IEEE International Symposium on Sustainable Systems and Technology 2011
DOI: 10.1109/issst.2011.5936908
|View full text |Cite
|
Sign up to set email alerts
|

The carbon footprint of watching television, comparing digital terrestrial television with video-on-demand

Abstract: This study estimated the carbon footprint of watching broadcast television using digital terrestrial television and online delivery of video-on-demand.The carbon footprint for digital terrestrial television was found to be 0.088 kg CO 2 e/viewer-hour and for online delivery of video-on-demand ranges from 0.030-0.086 kg CO 2 e/viewer-hour. This was based mainly on the energy consumption in the use phase. Results were sensitive to the number of viewers per display.It was found that the largest environmental impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…These costs were based on the running costs of servers [23] and current Intel [24] processors [25]. The emissions were calculated with the National Energy Foundation (NEF) carbon calculator for 2016 [26], and using the cheapest business rate for January 2017 of 10.5 pence per kWh for electricity [27].…”
Section: B Estimated Costs Of the Current Broadcast Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…These costs were based on the running costs of servers [23] and current Intel [24] processors [25]. The emissions were calculated with the National Energy Foundation (NEF) carbon calculator for 2016 [26], and using the cheapest business rate for January 2017 of 10.5 pence per kWh for electricity [27].…”
Section: B Estimated Costs Of the Current Broadcast Systemmentioning
confidence: 99%
“…Fully optimising the broadcast powers of the network is something that cannot easily be addressed during Manuscript received May 10, 2016; revised August 6, 2016, January 6, 2017 and January 20, 2017. Accepted January 23,2017. Figure 5 and related data has been reproduced from research previously presented in [1].…”
Section: Introductionmentioning
confidence: 99%
“…A 2011 BBC study [39] found that set-top boxes (the modems which deliver both cable TV and Internet connectivity) are on for 15.57 hours/day, but it did not address their usage time. A 2007 study found that in Europe, DSL modems are idle for 20 hours/day and in use for the remaining 4 hours/day [40].…”
Section: The Energy Intensity Of Cpe and Access Networkmentioning
confidence: 99%
“…Although this study is older, we use its assumptions. The study distinguishes between the on and idle state of modems, and we feel that the on-time of 24 hours/day from [40] better reflects reality than the 15.57 hours/day from the 2011 study [39]. With these assumptions, t On /t U se = 6.…”
Section: The Energy Intensity Of Cpe and Access Networkmentioning
confidence: 99%
“…This is because broadcast has fixed carbon costs that can be amortized over large audience sizes, whereas the carbon costs of streaming grows with each additional user [12]. Motivated by these observations, we ask whether the flexibility of on-demand viewing can be supported while still relying as much as possible on low-energy broadcast.…”
Section: Introductionmentioning
confidence: 99%